Comparative study between laparoscopic hysterectomy and abdominal hysterectomy for the treatment of early stage endometrial cancer - Bhattacharjee, Rumi; Dhungat, Nitin P.; Sheth, Vishal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Aim was to study the feasibility of total laparoscopic pan hysterectomy in patients with early stage endometrial cancer. Methods: Retrospective and prospective study of 100 patients with clinical early stage endometrial cancer was done in Bombay Hospital & Research Center over 3 years. 44 patients underwent total laparoscopic hysterectomy while 56 patients underwent abdominal pain hysterectomy. Pelvic lymphadenectomy was performed in patients with myometrium invasion greater than 50%, size of tumor >2 cm, non-endometroid pathology, Grade 3. Results: The mean operating time was 2 hours in the abdominal hysterectomy group and 2.5 hrs. In the laparoscopic group. Average blood loss was 350 ml in the abdominal (Abd) group & 250 ml in the laparoscopic (lap) group. Which was comparable. The abdominal hysterectomy group experienced more postoperative pain than the laparoscopy group. However, cost wise laparoscopy group incurred more expenditure than the abdominal group. Among the post-operative complications, nausea vomiting, paralytic ileus and wound dehiscence were significantly more in the abdominal group as compared to the laparoscopy group. Conclusions: Morbidity is much less in laparoscopy route compare to open abdominal hysterectomy with equivalent survival.